Soccer functional fitness training - Dost, H.; Hyballa, P.; te Poel, H.-D. (Meyer & Meyer Sport (UK) Ltd., 2016)
The world`s best soccer players are incredibly fit, fast, lean, and strong. Achieving this level of athleticism requires a rigorous soccer fitness training program applying the most effective drills, exercises, and core training methods. In Soccer: Functional Fitness Training, the authors present numerous drills for this training. Based on the latest the findings in sports science and on the authors` long-term coaching experience, they present an extensive practical guide to help you improve your team`s performance through core training, soccer specific exercises, and drills. The exercises can be used for amateurs and professional players, youth and adults alike. Your players can learn how to score the most exciting and acrobatic goals, how to tackle without fouling, and how to avoid injuries. The drills in the book create typical match situations to help your team prepare for the game and stay motivated. Many of the fitness exercises require no extra equipment and rely only on bodyweight, thus targeting many different muscles at once. The book is easy to use on the pitch and the ideal tool to turn youth players into the next Cristiano Ronaldo, Zlatan Ibrahimovic, or Bastian Schweinsteiger.